Worries about the Economy: Income Inequality and Life Satisfaction - Lima-Nunes, Aline; De Andrade, Alexsandro; Azevedo da Cunha, Douglas (Revista de Psicología, 2021)
Financial situations affect people’s lives directly and indirectly. Phenomena such as unemployment and perceived income disparity embed negative consequences on objective and subjective dimensions of life. In this study, the mediating role played by economic worries was analysed in the relationship between income inequality and life satisfaction in Brazil. A total of 278 college students participated in this study (age: M = 23.71; SD = 7.31). Sociodemographic issues and the family income as a proxy to income inequality, measures of life satisfaction, and economic worries were used, as well as a subjective question about the relationship between these variables. Results showed that the relationship between family income and life satisfaction was mediated by personal economic worries (not Brazilians economic worries). One category stood out in the content analysis on the open question: Economic worries as the determinant of Brazilians’ life satisfaction (39.7%). Together these results portray the relevance of the economic worries as the definition of life satisfaction, especially in college students, showing that the direct relationship between income inequality and life satisfaction is affected by the perception about personal/familiar economy.